Comportamento elétrico, mecânico e hidráulico de um sistema de bombeamento sob o enfoque da eficiência energética - Guimarães, Ronaldo (2008)
This thesis aims to present a methodology for comparing the performance electrical, mechanical and hydraulic under the focus of the energy efficiency of pumping systems controlled by valves of strangulation or by the frequency converters. The trigger is held by engines of the line standard or high efficiency. Therefore, this paper presents the simulation in domain of time from a computer platform called ATP (Alternative Transient Program). Complementing the aspects earlier, the validation of proposal modeling, is performed by comparing the simulated values and those from the tests. Finally, it should be emphasized that the laboratory experiments were performed in the laboratory for energy efficiency of the Faculty of Electrical Engineering of the Federal University of Uberlândia.